2007
DOI: 10.1103/physrevlett.98.135701
|View full text |Cite
|
Sign up to set email alerts
|

Shock Waves in Polycrystalline Iron

Abstract: The propagation of shock waves through polycrystalline iron is explored by large-scale atomistic simulations. For large enough shock strengths the passage of the wave causes the body-centered-cubic phase to transform into a close-packed phase with most structure being isotropic hexagonal-close-packed (hcp) and, depending on shock strength and grain orientation, some fraction of face-centered-cubic (fcc) structure. The simulated shock Hugoniot is compared to experiments. By calculating the extended x-ray absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
125
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 21 publications
7
125
0
1
Order By: Relevance
“…However, the pressures involved are comparable to those of other high-energy processes, such as laser ablation, high-energy impact and diamond anvil cells. [1][2][3][4][5][6][7][8][9] This suggests that further work is needed to improve the description of atomic force fields at short interatomic distances in order for future computational work using these force fields to be as quantitatively accurate as possible. Some efforts have previously been made in this direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pressures involved are comparable to those of other high-energy processes, such as laser ablation, high-energy impact and diamond anvil cells. [1][2][3][4][5][6][7][8][9] This suggests that further work is needed to improve the description of atomic force fields at short interatomic distances in order for future computational work using these force fields to be as quantitatively accurate as possible. Some efforts have previously been made in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…1 Notably, such computational results explain the Newton rings observed in experiments. 2,3 MD also led to a better understanding of the nature of the destructive shockwaves that follow high-energy impact [4][5][6] and the behavior of materials at high pressure in diamond anvil cells. [7][8][9] It can predict many properties, such as the Hugoniot, dislocation densities after impact and fracture behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Проводятся экспериментальные исследования и моделирование как специально создаваемых композитных и малоплотных материалов, так и естественных поликристалли-ческих образцов. Исследования, главным образом, сконцентрированы на определении интегральных оп-тических, электрических, тепловых, акустических, прочностных характеристик как самих материалов [3,4], так и изделий из них, а также на соотношении наблюдаемых эффектов с параметрами диодной плаз-мы, летящей с поверхности исследуемого образца. Отличительной чертой данного проекта будет визуа-лизация распространения возмущений в гетерогенной среде, которая позволит изучать различные режи-мы радиационного воздействия на мишени и мелкие, но важные пространственные особенности этого процесса в эксперименте, в то время как обычно для получения сведений о пространственных распреде-лениях параметров используют только численное моделирование [5,6].…”
Section: Introductionunclassified
“…The ε-Fe phase is nonmagnetic (the magnetic moment is equal to zero). Later, iron of this syngony was obtained by other scientists [3][4][5][6][7][8][9][10][11][12], but high pressures were used in all the methods. J.C. Jamieson suggested that, although the formation of the ε-Fe phase is most easy to carry out under nonhydrostatic conditions, but abnormal distortions under compression allow hoping for the possibility of the formation of ε-Fe under hydrostatic conditions, too.…”
Section: Overviewmentioning
confidence: 99%